Flat building blocks for flat silicene - Takahashi, Masae (Sci Rep, 2017)
Silicene is the silicon equivalent of graphene, which is composed of a honeycomb carbon structure with one atom thickness and has attractive characteristics of a perfect two-dimensional π-conjugated sheet. However, unlike flat and highly stable graphene, silicene is relatively sticky and thus unstable due to its puckered or crinkled structure. Flatness is important for stability, and to obtain perfect π-conjugation, electron-donating atoms and molecules should not interact with the π electrons. The structural differences between silicene and graphene result from the differences in their building blocks, flat benzene and chair-form hexasilabenzene. It is crucial to design flat building blocks for silicene with no interactions between the electron donor and π-orbitals. Here, we report the successful design of such building blocks with the aid of density functional theory calculations. Our fundamental concept is to attach substituents that have sp-hybrid orbitals and act as electron donors in a manner that it does not interact with the π orbitals. The honeycomb silicon molecule with BeH at the edge designed according to our concept, clearly shows the same structural, charge distribution and molecular orbital characteristics as the corresponding carbon-based molecule.